THE HISTORY OF STUDYING THE FRONT LETTERS OF UZBEK PARTICIPANTS IN THE SECOND WORLD WAR - Rufina Ravilevna Kayumova (Journals Park Publishing, 2022)
The article analyzes the letters of soldiers and officers participating in the Second World War. It also explores the cultural and communicative functions of epistolary messages based on archival materials.
Keywords: World War II, Motherland, epistolary text, letters, ideology, historical source, regulations, newspaper, envelope, source complex.